E-Governance and Its Impact on Common Populace - Masood, Rana Zehra (Journal of Commerce and Trade, 2011)
All over the world, the spectacular growth and development of information and communication Technology (ICTs) has changed the total scenario of our daily life and their subsequent use on strengthening interaction among public entities, civil societies, communities and citizens has given rise to a new governance paradigm known as E-Governance. Electronic Governance (e-Governance) is the application of information & communication technologies to transform the efficiency, effectiveness, transparency and accountability of informational & transactional exchanges with in Government, between govt. & govt. agencies of National, State, Municipal & Local levels, citizen & businesses, and to empower citizens through access & use of information” Presently, E-Governance is more than a Government website on the internet. Political, social, economic and technological aspects determine the scope and success of existence of E-Governance. It may include a broad range of services for many segments of society. The most common areas of e-Governance application are electronic commerce and business regulations, taxation and revenue, law enforcement and courts, education, health and transport. E-Governance facilitates a competent, speedy and translucent procedure to disseminate information to the public and other agencies, and to execute Government administration activities. A lot of initiatives have already been taken in the area, but specialists clamour for things to be implemented. A lot of measures are still to be taken for authenticity and confidence in online transactions. This paper intended to focus on the objectives, scope, initiatives taken by E-Governance together with challenges faced during the implementation and Recommendations to overcome these challenges.